Controlling the formation and alignment of low molecular weight gel 'noodles'. Issue 70 (11th August 2021) - McDowall, Daniel; Walker, Matthew; Vassalli, Massimo; Cantini, Marco; Khunti, Nikul; Edwards-Gayle, Charlotte Jennifer Chante; Cowieson, Nathan; Adams, Dave J.
Abstract : Extensional deformations induce nanostructure alignment in low molecular weight gel noodles during injection. Abstract : We show how to control the formation and alignment of gel 'noodles'. Nanostructure alignment can be achieved reproducibly by extensional deformation as the filaments form. Using a spinning technique, very long and highly aligned filaments can be made. The Young's moduli of the gel noodles are similar to that of a bulk gel. By using two syringe pumps in a concentric flow setup, we show that a filament-in-filament morphology can be created.